DECENT WORK AND COFFEE SECTOR: ARE THE COFFEE ESTATES IN KENYA COMPLYING WITH DECENT WORK IN PRODUCTION AND PRIMARY PROCESSING? - Munyentwari Mbuta, Joseph; K Hillary, Bett; Jerop, Rebecca (Applied Studies in Agribusiness and Commerce, 2024)
Coffee plays a big role in Kenya, it contributes to 30 percent of agricultural jobs and country’s exports. However, casual workers within coffee estates still get challenging employment conditions including long working hours, unfair wages, limited social capacity, and lack of collective bargaining that results in poor living standards and job insecurity. And also, no research shows compliance with decent work in the Kenyan coffee sector. This study sought to provide new literature about decent work compliance in production and primary processing within Coffee estates in Kiambu county. Snowballing sampling method was used to collect data among 385 casual workers from EAAGADS, Fairview, Maakiou, and Magumu coffee estates. Descriptive statistics and inductive logic were used to generate decent work indices from statistical indicators explaining each decent work pillar. Decent work indices 0.41 and 0.44 show the low compliance of social dialogue and safety at workplace dimensions respectively. Results, also show that effort has been done under productive employment and social protection dimension as shown by indices of 0.65 and 0.51 respectively. Moreover, there is a need for ILO inspection to ensure whether there is a promotion of decent work practices within coffee production to promote the living standards of coffee casual workers and also the stimulation of sustainable development of the County as well as the Country.